Effects of genotype x environment interaction on soybean yield in Paraná State, Brazil - Alliprandini, Luis Fernando; de Toledo, José Francisco Ferraz; Jr., Nelson Fonseca; de Almeida, Leones Alves; Kiihl, Romeu Afonso de Souza (Pesquisa Agropecuaria Brasileira, 1994)
The environmental and the environmental x genotype interaction effects acting upon soybean genotypes were evaluated from data of yield trials carried out in Paraná State, Brazil, in the period from 1987 to 1990. Data involved three maturity groups: early (L), semi-early (M) and average (N), that together represent over 90% of the soybean cropped area. Soybean produtivity has been shown to be highly influenced by the environment, defined by the interaction of year and location effects. No main year or location effects were found to be significant. The significance of the interaction between years and locations indicated that the yield tests should be performed in several environments. Abbreviation of the testing period, to a year for example, is feasible if sev-eral locations are included in the evaluation. Locations such as Ponta Grossa, Palotina, Congoinhas, Guarapuava and Castro produced consistent evaluations. Cascavel, Ponta Grossa and Sertaneja discriminated between tested genotypes better than other locations. These locations should be included in the soybean yield test to improve testing reliability in Paraná State.